2020
DOI: 10.21580/jiafr.2020.2.2.6357
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect on inflation, interest rate, dow jones Islamic Malaysia Index and profitability on stock prices as selected as Indonesia Sharia Stock Index

Abstract: Purpose - The purpose of this study was to analyze what influences the change in the ISSI price index. The analysis was based on the phenomena and hypotheses that occur in the capital market by examining whether there is an influence of inflation rates, interest rates, and the Dow Jones Islamic Malaysia Index as external factors, as well as profitability such as Return on Assets and Earning per Share as internal factors that have an influence on changes and fluctuations in the Sharia Stock Index.Method - The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Studies have found that inflation rates can affect the returns of both Islamic and conventional stock markets, with some research indicating a positive long-term relationship between inflation and stock market returns (Jelilov, Iorember, Usman, & Yua, 2020;Kwofie & Ansah, 2018). However, other studies suggest that inflation may have a negative impact on the Sharia Stock Market index in the short term, especially during economic shocks such as the COVID-19 pandemic (Halim, 2020;Suriani, Nasir, & Ernawati, 2022).…”
Section: Inflation and Sharia Stock Marketmentioning
confidence: 99%
“…Studies have found that inflation rates can affect the returns of both Islamic and conventional stock markets, with some research indicating a positive long-term relationship between inflation and stock market returns (Jelilov, Iorember, Usman, & Yua, 2020;Kwofie & Ansah, 2018). However, other studies suggest that inflation may have a negative impact on the Sharia Stock Market index in the short term, especially during economic shocks such as the COVID-19 pandemic (Halim, 2020;Suriani, Nasir, & Ernawati, 2022).…”
Section: Inflation and Sharia Stock Marketmentioning
confidence: 99%
“…Pengaruh variabel ekonomi makro terhadap indeks saham konvensional dieksplorasi dalam penelitian oleh Candy & Winardy (2019), Ranto (2019), Sinay et al (2018) dan Thamrin & Sembel (2020). Sebuah studi yang meneliti dampak variabel ekonomi makro pada indeks saham syariah diteliti oleh Ahmed et al (2018), Kumar & Sahu (2018), Mashudi et al (2020), Halim (2020) dan Junaidi et al (2021). Studi sebelumnya mengasumsikan bahwa karakteristik pasar yang berbeda menyebabkan perilaku dan risiko pasar yang berbeda.…”
Section: Pendahuluanunclassified
“…OJK Regulation Number 15/PJOK.04/2015 concerning Application of Sharia Principles in the Capital Market states that Sharia Securities are Securities as referred to in the Capital Market Law and its implementing regulations, operating procedures, business activities; the assets that form the basis of the contract, and/ or assets related to the said Securities and their issuers do not conflict with the Sharia Principles. Sofyan Halim (2020), quoting from idx.co.id, and Nur Imamah, Tsui-Jung Lin, Suhadak, Siti Ragil Handayani, Jung-Hua Hung (2019), stated that the Indonesian Sharia Stock Index (ISSI) is a composite stock index sharia shares listed on the IDX and began to be issued on May 12, 2011. ISSI is an indicator of the performance of the Indonesian sharia stock market.…”
Section: Indonesian Sharia Stock Indexmentioning
confidence: 99%
“…The development of global Islamic stock indices, including the Dow Jones Syariah Market Index, has quite influenced the development of portfolio investment in various global exchanges, including in Indonesia, and this has also affected the Islamic stock market price, based on the results of research by Retno Fuji Oktaviani (2017), and Halim (2020) who examined International Sharia Stock Price Index against the Jakarta Islamic Index. The conclusion of the study shows that JII is significantly influenced by DJII USA and DJIM.…”
Section: Introductionmentioning
confidence: 99%